Cannabis, cannabinoids, and health. Issue 3 (30th September 2017) - Lafaye, Genevieve; Karila, Laurent; Blecha, Lisa; Benyamina, Amine
Abstract : Cannabis (also known as marijuana) is the most frequently used illicit psychoactive substance in the world. Though it was long considered to be a "soft" drug, studies have proven the harmful psychiatric and addictive effects associated with its use. A number of elements are responsible for the increased complications of cannabis use, including the increase in the potency of cannabis and an evolution in the ratio between the two primary components, Δ 9 -tetrahydrocannabinol (Δ 9 -THC) and cannabidiol (toward a higher proportion of Δ 9 -THC), Synthetic cannabinoid (SC) use has rapidly progressed over the last few years, primarily among frequent cannabis users, because SCs provide similar psychoactive effects to cannabis. However, their composition and pharmacological properties make them dangerous substances. Cannabis does have therapeutic properties for certain indications. These therapeutic applications pertain only to certain cannabinoids and their synthetic derivatives. The objective of this article is to summarize current developments concerning cannabis and the spread of SCs. Future studies must further explore the benefit-risk profile of medical cannabis use.